Multi-omics reveals EGCG’s anti-calcification effects associated with gut microbiota and metabolite remodeling - Zhang, Yating; Tang, Zihan; Zhu, Junwen; Zhao, Ruochi; Wang, Shuangshuang (Frontiers in Immunology, 2025)
IntroductionVascular calcification, a pathological process driven by heterotopic calcium-phosphate deposition, arises from vascular smooth muscle cells (VSMCs) osteochondrogenic transformation, epigenetic dysregulation, and metabolic reprogramming. Epigallocatechin-3-gallate (EGCG), a natural polyphenol, is associated with attenuated vascular calcification and remodeling of the gut microbiota-metabolite axis.MethodsTwenty-four 8-week-old Sprague-Dawley rats were randomized into four groups: control (CON), vitamin D3-induced calcification (VD), VD plus EGCG (VD+EGCG), and EGCG-only (EGCG). Vascular calcification was induced via vitamin D3 injection, followed by 11-week EGCG treatment. Calcification severity was quantified using alizarin red S staining, alkaline phosphatase (ALP) immunohistochemistry/immunofluorescence, and serum metabolomics, while colon microbiota and metabolites were profiled via 16S rRNA sequencing and LC-MS/MS.ResultsEGCG significantly reduced calcification (*P<0.05 vs. VD), as evidenced by diminished alizarin red S staining and suppressed ALP activity. Gut microbiota analysis revealed EGCG-mediated restoration of alpha diversity and taxonomic shifts, including reversal of Spirochaetota, Desulfobacterota, and Actinobacteriota abundances at the phylum level (*P<0.05); marked changes in Clostridia_UCG_014, Desulfovibrionales, Christensenellales, Erysipelotrichales, Oscillospirales, and Spirochaetales at the order level (*P<0.05); and normalization of Treponema, unclassified Treponema, and Lactobacillus johnsonii at the genus/species level (*P<0.05). Serum metabolomics identified VD3-induced upregulation of phospholipid metabolites (phosphatidylserine [PS], phosphatidylcholine [PC], lysophosphatidylcholine [LysoPC]), which were counteracted by EGCG (*P<0.05). Concurrently, EGCG enhanced ubiquinone biosynthesis and terpenoid-quinone pathways.DiscussionThese changes are mechanistically linked to suppressed VSMCs osteogenic differentiation and aortic degeneration. The findings establish EGCG as a dual microbiota-metabolite modulator with therapeutic potential for vascular calcification, offering a novel strategy to target gut-vascular crosstalk in cardiovascular disease.